The Impact Of Special Economic Zones On Dropout Rates At The Junior And Senior High School Levels In Indonesia - Sandey Cristiany Sihombing; Khoirunurrofiq Khoirunurrofiq (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to analyze the impact of the presence of Special Economic Zones (SEZs) on dropout rates at the junior and senior high school levels in Indonesia. SEZs are place-based policies designed to increase investment, create job opportunities, and stimulate economic growth. However, the increase in job opportunities due to the presence of SEZs may encourage individuals to prioritize working over continuing their education. This study uses panel data from districs/cities in 14 provinces with special economic zones. The study employs the Difference-in-Differences method to estimate differences in school dropout rates between regencies with SEZs and those without. The findings indicate that the presence of special economic zones does not have a significant impact on dropout rates at the junior and senior high school levels in Indonesia.Additionally, this study applies the Propensity Score Matching method to minimize selection bias in determining the control group. The estimation results also indicate that the presence of special economic zones does not have a significant impact on dropout rates at the junior and senior high school levels in Indonesia.